2022
DOI: 10.1007/s00424-022-02713-8
|View full text |Cite
|
Sign up to set email alerts
|

AMPK facilitates the hypoxic ventilatory response through non-adrenergic mechanisms at the brainstem

Abstract: We recently demonstrated that the hypoxic ventilatory response (HVR) is facilitated by the AMP-activated protein kinase (AMPK) in catecholaminergic neural networks that likely lie downstream of the carotid bodies within the caudal brainstem. Here, we further subcategorise the neurons involved, by cross-comparison of mice in which the genes encoding the AMPK-α1 (Prkaa1) and AMPK-α2 (Prkaa2) catalytic subunits were deleted in catecholaminergic (TH-Cre) or adrenergic (PNMT-Cre) neurons. As expected, the HVR was m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…Previously, targeted deletion of AMPK-α1 and AMPK-α2 in brainstem catecholaminergic cells through Cre expression via the tyrosine hydroxylase promoter (TH-AMPK-α1/α2 knockout) was confirmed by single-cell end-point PCR, by viral injection of a Cre-inducible vector carrying a reporter gene [ 59 ] and by crossing TH-AMPK-α1/α2 knockout mice with mice engineered for Cre-dependent expression of Rosa (tdTomato) and subsequent analysis by confocal imaging of caudal brainstem areas [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Previously, targeted deletion of AMPK-α1 and AMPK-α2 in brainstem catecholaminergic cells through Cre expression via the tyrosine hydroxylase promoter (TH-AMPK-α1/α2 knockout) was confirmed by single-cell end-point PCR, by viral injection of a Cre-inducible vector carrying a reporter gene [ 59 ] and by crossing TH-AMPK-α1/α2 knockout mice with mice engineered for Cre-dependent expression of Rosa (tdTomato) and subsequent analysis by confocal imaging of caudal brainstem areas [ 57 ].…”
Section: Resultsmentioning
confidence: 99%
“…The overall shape of the DAR indicated that several anatomical subnuclei of the NTS were likely affected by AMPK deficiency. Surprisingly, AMPK deletion and subsequent reductions in neuronal activity within the DAR were associated with attenuation of the hypoxic ventilatory response (HVR) at the peak of the augmenting phase (~ 30 s), roll-off (~ 100 s) and the sustained phase (~ 100 s) [ 56 , 57 , 59 ] , but not cardiovascular responses to hypoxia [ 56 ]. This is despite the fact that both cardiovascular and respiratory compartments of the ventrolateral medulla (VLM) are in receipt of NTS afferent inputs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Special Issue unites four comprehensive reviews on somatic feedback signals and brain function, covering its potential cognitive-behavioral significance [12,17], the role of slow (respiratory) nasal feedback signals for brain dynamics [19] and the role of rhythmic oxygen pressure oscillations for potential neuronal effects of respiration [39]. Five original articles address specific effects of respiration on gamma oscillations [14], the state-dependence of respiration-cortical activity coupling [18], entrainment of brainstem neurons of the reticular formation by cardiac activity Kocsis and Topchyi [23], the molecular mechanisms linking hypoxia-mediated activation of carotid bodies to increased ventilation [25] and a new neuromodulatory effect on respiratory rhythm generation in brainstem networks by the peptide bombesin [27]. Finally, a systematic literature review summarizes the evidence for, or against, consistent changes of pupil diameter with respiration.…”
mentioning
confidence: 99%